2016
DOI: 10.15226/jnhfs.2016.00166
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Nutritional Quality and Consumer Acceptability of Wheat-Sesame (Triticum aestivum-Sesame indicum) Composite Bread Blends

Abstract: seed flour inclusion in bread making has the ability to improve the physicochemical, sensory characteristics and micronutrient content of the composite samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The improvement in the loaf volume, loaf weight and specific volume could be attributed to the increase in structure forming proteins in the sesame flour added which could have enhanced the ability of the dough to rise during proofing resulting in an increase the bread volume (Bibiana et al,2014). Lombor et al,(2016) found that substituting whole wheat flour with up to 20% sesame seed flours would significantly (p<0.05) improve the loaf volume, loaf weight and specific volume.…”
Section: Physical Properties Of Prepared Pan Breadmentioning
confidence: 93%
“…The improvement in the loaf volume, loaf weight and specific volume could be attributed to the increase in structure forming proteins in the sesame flour added which could have enhanced the ability of the dough to rise during proofing resulting in an increase the bread volume (Bibiana et al,2014). Lombor et al,(2016) found that substituting whole wheat flour with up to 20% sesame seed flours would significantly (p<0.05) improve the loaf volume, loaf weight and specific volume.…”
Section: Physical Properties Of Prepared Pan Breadmentioning
confidence: 93%